Novel layered iron antimony thiostannate adsorbent of K1.61Fe0.04Sb0.03Sn3.1S7 for cesium green recovery from geothermal water. (1st May 2022) - Jiang, Zhenzhen; Ma, Chi; He, Yanqing; Li, Mingli; Liu, Gaoling; Guo, Yafei; Ji, Duo; Deng, Tianlong
Abstract: To develop a green and efficient cesium adsorbent with high adsorption capacity, rapid kinetics, and good regeneration performance is a tremendous challenge. In this work, potassium iron antimony thiostannate (PIATS) synthesized by the hydrothermal method was utilized for green recovery cesium from geothermal water for the first time. PIATS showed a high adsorption capacity of 401.23 mg/g, which was much higher than other types of adsorbents at present. Meanwhile, PIATS showed rapid ion exchange kinetics (within 3 min) and broad pH resistance (4–12). More importantly, PIATS still showed excellent selectivity to cesium even in geothermal water containing many other coexisted ions ( K d  = 1.96 × 10 4  mL/g), and the separation factors between Cs + and the coexisted competing ions were ranged from 462.77 to 963.76. Subsequently, the cesium-laden PIATS could be easily eluted with 0.50 mol/L NaNO3 to achieve rapid desorption (within 10 min). The concentration of Cs + in the elution was enriched more than 11 times higher than that in the original solution. Furthermore, no organic solvents or other toxic reagents were involved during the whole process. Therefore, the adsorption advantages, excellent enrichment ability, and structural stability of PIATS make it a potential recyclable candidate for green cesium recovery from geothermal water. Graphical abstract: Image 1 Highlights: Novel metal sulfide adsorbent PIATS was synthesized for Cs +  recovery from geothermal water. High adsorption capacity (401.23 mg/g) and ultrafast adsorption rate (3 min) were achieved. Separation factors between Cs + and Na +, K +, Li +, Ca 2+ were ranged from 462.77 to 963.76. Green high performance of elution and regeneration of NaNO3 at neutral was found.